The effect of financial literacy on student financial behavior at the Sumatera Selatan University - Teuku Muhammad Haqiqi; Santi Oktavianti; Jabarti Jabarti; Muhammad Shalahuddin; Henny Oktaviyani (Jurnal Mantik, 2024)
Financial literacy is the skill to separate financial problems and financial alternatives. Managing money is very necessary in everyday life, and the ability to financial behavior that is owned independently without supervision and control from parents. The research study analyzed the characteristics of the population at the University of South Sumatra students using population sampling, probability sampling, and accidental sampling techniques. Data sources include primary and secondary, and sampling techniques include questionnaires and Likert. The findings inform future research and policy decisions, examining sociological phenomena and their impact on the population. The significant value in the regression test of the estimated r value was higher than the r table value, demonstrating that financial literacy has a beneficial influence on students' financial behavior in the Management Study Program at the University of South Sumatra. Therefore, the H1 hypothesis is accepted and it can be said that there is a strong influence between financial literacy (X) on financial behavior (Y) in students of the university of South Sumatra, Faculty of Economics, Management study program. Research limitations on data collection time. This research is expected to be able to provide references for future researchers.